Water purification from metal ions in the presence of organic matter using electromagnetic radiation-assisted treatment. (20th January 2021) - Hashim, Khalid S.; Shaw, Andy; AlKhaddar, Rafid; Kot, Patryk; Al-Shamma'a, Ahmed
Abstract: Organic matter is a widely occurring pollutant in freshwater sources due to the extensive use of synthetic organic compounds in industry and the natural occurrence of organic matter in the Earth's crust. Organic matter causes adverse effects on the performance of water treatment plants, such as accelerated bacterial growth and increased consumption of chemical coagulants. Organic matter also has the ability to chelate some heavy metals forming refractory complexes that resist coagulation. The current research combines electromagnetic radiation (microwave) and electrocoagulation technologies to purify water from OM-heavy metal complexes created using iron and ethylenediaminetetraacetic acid (EDTA). The organic matter-iron solution was introduced to a microwave field to break down the complex, followed by electrolysis of the solution using an aluminum-base EC cell. Microwave power (50.0–300.0 W), temperature (50.0–150.0 °C) and irradiation period (5.0–15.0 min) were measured. During the electrolysing stage, initial pH (4.0–8.0), current density (1.0–2.0 mA cm −2 ) and space between electrodes (5.0–20.0 mm), were examined. The results showed that the electromagnetic radiation-electrocoagulation technology removed up to 92% of the organic matter-iron complex in comparison to 69.6% removal using a traditional electrocoagulation method. The best operational conditions were established as follows: 10 min of microwave irradiation at 100 Wat a temperature of 100 °C, followed by 20.0 min of electrolysing at an initial pH of 6.0, the space between electrodes 5.0 mm and current density of 1.50 mA cm −2 . Graphical abstract: Image 1 Highlights: Presence of OM decreases the removal of heavy metals using the EC method by about 80%. The EC unit cannot remove more than 69% of heavy metals in presence of OM. Emerging the EC with the MW could increase the removal heavy metals, in the presence of OM, up to 92%. Power, duration and temperature of the MW fields play a significant role in the removal of heavy metals.